Relationship between perceived organizational politics, organizational trust, selected human resource management practices and turnover intention among Nigerian nurses - Abdulkareem, Ramatu Abubakar (2014)
Prior research has indicated that employee turnover is detrimental to both individuals and organisations. Because a turnover intention in the workplace is detrimental, several factors have been suggested to better understand the reasons why employees may decide to leave their organisations. Some of the organizational-related factors that have been considered by previous research include perceived organizational justice, job satisfaction, perceived psychological contract breach, and perceived organizational support, among others. Despite these empirical studies, literatures indicate that less attention has been paid to the influence of perceived organisational politics, organizational trust, and perceived human resource practices management (HRM) practices on employee turnover. Hence, the present study fills in the gap by examining the relationship between perceived organisational politics, organizational trust, perceived human resource management practices and employee turnover among Registered Nurses in Nigerian public hospitals using multiple regression analysis technique. One hundred and seventy five Registered Nurses participated in the study. Result indicated that perceived organisational politics was significantly and positively related to turnover intentions. The result also showed that both organizational trust and perceived human resource practices were significantly and negatively related to turnover intentions. Furthermore, the result showed that male nurses were more likely to leave their organizations or the profession than their female colleagues. Younger nurses were more likely to leave their organizations or the profession than their older colleagues. Theoretical and practical implications of the results are discussed.